Implications of habitual endurance and resistance exercise for dynamic cerebral autoregulation - Perry, B. G.; Cotter, J. D.; Korad, S.; Lark, S.; Labrecque, L.; Brassard, P.; Paquette, M.; Le Blanc, O.; Lucas, S. J. E. (Experimental Physiology, 2019)
New Findings What is the central question of this study? Does habitual resistance and endurance exercise modify dynamic cerebral autoregulation? What is the main finding and its importance? To the authors` knowledge, this is the first study to directly assess dynamic cerebral autoregulation in resistance-trained individuals, and potential differences between exercise training modalities. Forced oscillations in blood pressure were induced by repeated squat-stands, from which dynamic cerebral autoregulation was assessed using transfer function analysis. These data indicate that dynamic cerebral autoregulatory function is largely unaffected by habitual exercise type, and further document the systemic circulatory effects of regular exercise.